1
0
Fork 0

Updated syntax.

This commit is contained in:
Luc Bijl 2023-11-22 10:46:03 +01:00
parent 5de172cdb6
commit 70ea333730

View file

@ -1,6 +1,6 @@
# Logic
*Definition*: a statement is a sentence that is either true or false, never both.
> *Definition*: a statement is a sentence that is either true or false, never both.
<br>
@ -12,32 +12,32 @@
<br>
*Definition* **- Implies**: if $A$ and $B$ are assertions then the assertion if $A$ then $B$ ($A \implies B$) is true iff
* $A$ is true and $B$ is true,
* $A$ is false and $B$ is true,
* $A$ is false and $B$ is false.
This also works the opposite way, if $B$ then $A$ ($A \Longleftarrow B$)
> *Definition* **- Implies**: if $A$ and $B$ are assertions then the assertion if $A$ then $B$ ($A \implies B$) is true iff
>
> * $A$ is true and $B$ is true,
> * $A$ is false and $B$ is true,
> * $A$ is false and $B$ is false.
>
> This also works the opposite way, if $B$ then $A$ ($A \Longleftarrow B$)
<br>
*Definition* **- If and only if**: if $A$ and $B$ are assertions then the assertion $A$ if and only if $B$ (A \iff B) is true iff
> *Definition* **- If and only if**: if $A$ and $B$ are assertions then the assertion $A$ if and only if $B$ (A \iff B) is true iff
>
> * $(A \Longleftarrow B) \land (a \implies B)$.
>
> This leads to the following table.
* $(A \Longleftarrow B) \land (a \implies B)$.
: This leads to the following table.
| $A$ | $B$ | $A \implies B$ | $A \Longleftarrow B$ | $A \iff B$|
| :---: | :---: | :------------: | :------------------: | :-------: |
| true | true | true | true | true |
| true | false | false | true | false |
| false | true | true | false | false |
| false | false | true | true | true |
| $A$ | $B$ | $A \implies B$ | $A \Longleftarrow B$ | $A \iff B$|
| :---: | :---: | :------------: | :------------------: | :-------: |
| true | true | true | true | true |
| true | false | false | true | false |
| false | true | true | false | false |
| false | false | true | true | true |
<br>
*Definition*: suppose $P$ and $Q$ are assertions. $P$ implies $Q$ if $P \implies Q$ is true. $P$ and $Q$ are equivalent if $P$ implies $Q$ and $Q$ implies $P$.
> *Definition*: suppose $P$ and $Q$ are assertions. $P$ implies $Q$ if $P \implies Q$ is true. $P$ and $Q$ are equivalent if $P$ implies $Q$ and $Q$ implies $P$.
## Methods of proof